The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/nano11010160
|View full text |Cite
|
Sign up to set email alerts
|

Coating of Conducting and Insulating Threads with Porous MOF Particles through Langmuir-Blodgett Technique

Abstract: The Langmuir-Blodgett (LB) method is a well-known deposition technique for the fabrication of ordered monolayer and multilayer thin films of nanomaterials onto different substrates that plays a critical role in the development of functional devices for various applications. This paper describes detailed studies about the best coating configuration for nanoparticles of a porous metal-organic framework (MOF) onto both insulating or conductive threads and nylon fiber. We design and fabricate customized polymethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…86 The choice of MOF candidates that can be adopted via this approach are with less limitations, even including high-valence metal based MOFs such as MIL-101(Cr), MIL-96(Al) and UiO-66. [88][89][90][91][92] The quality of the resulting lms highly depends on the homogeneity of the MOF suspension, where the choice of the dispersant and surfactant can be crucial. 89,90 In this strategy, the MOF suspensions are deposited onto at substrates, aer which solvent evaporates leading to uniform and polycrystalline lms.…”
Section: Colloidal Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…86 The choice of MOF candidates that can be adopted via this approach are with less limitations, even including high-valence metal based MOFs such as MIL-101(Cr), MIL-96(Al) and UiO-66. [88][89][90][91][92] The quality of the resulting lms highly depends on the homogeneity of the MOF suspension, where the choice of the dispersant and surfactant can be crucial. 89,90 In this strategy, the MOF suspensions are deposited onto at substrates, aer which solvent evaporates leading to uniform and polycrystalline lms.…”
Section: Colloidal Depositionmentioning
confidence: 99%
“…In a recent study, Rauf et al reported a homogenous coating of MIL-96(Al) monolayer thin films onto conductive and insulating polymer threads, evidencing the applicability of this approach to a wide choice of substrates. 91 The deposited films possess the hierarchical microporosity from the MOF and additional meso- to macro-porosity from assembled MOF particles. 40 Moreover, the film thickness is often controllable by tuning the particle size of deployed MOFs, the concentration and viscosity of the MOF suspension, as well as deposition parameters ( e.g.…”
Section: Patterning Techniques Of Mof Thin Filmsmentioning
confidence: 99%
“…In this study, by Rauf et al, customized polymethylmethacrylate sheets (PMMA) holders to deposit MOF layers onto the threads or fiber using the LB technique were designed and fabricated. The results demonstrate a significant contribution in terms of MOF monolayer deposition onto single fiber and threads that will contribute to the fabrication of single fiber or thread-based devices in the future [ 1 ].…”
mentioning
confidence: 99%